Anxiety and depression symptoms in family members of icu patients (2015)
Objective: This study investigated symptoms of anxiety and depression in relatives of patients admitted in the Intensive Care Unit and determined whether these symptoms were associated to the seriousness of the patients’ condition.Metodology: A total of 102 patients’ relatives were surveyedduring the study. They were given a self-report questionnaire in order to assess demographic data, anxiety and depression symptoms. The symptoms of anxiety and depression were evaluated with the Hospital Anxiety and Depression Scale (hads). Patient’s condition was evaluated with a.p.a.ch.e ii Score.Results: More than 60% of patients’ relatives presented severe symptoms of anxiety and depression. No relation was found between symptoms of anxiety and depression of the relatives of patients and patients’ condition of health. On thecontrary, these feelings used to exist regardless of the seriousness of patient’s condition.Conclusions: The assessment of these patients is recommended in order serious problems of anxietyand depression to be prevented.